2018
DOI: 10.1128/aem.00292-18
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Visualization of Internalized Human Norovirus in Leafy Greens

Abstract: Lettuce has been implicated in human norovirus (HuNoV) outbreaks. The virus is stable on the leaf surface for at least 2 weeks; however, the dynamics of virus internalization have not been fully investigated. The purpose of this study was to assess the internalization and distribution of HuNoV and two surrogate viruses, porcine sapovirus (SaV) and Tulane virus (TV), in lettuce and spinach. Viral inoculations through the roots of seedlings and the petiole of leaves from mature plants were performed, and the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Fecal filtrates from GII.4 Sydney[P16] and GII.4 Sydney[P4 New Orleans] human norovirus-positive fecal samples were prepared by passing clarified stool extracts through four serial filters (5, 1, 0.45, and 0.22 μm) as described previously ( Costantini et al, 2018 ) and stored at −70°C until the time of testing. Tulane virus was grown in LLC-MK2 cell line (ATCC CCL-7) cultured in Opti-MEM (Gibco Life Technologies, Grand Island, NY) supplemented with 2% FBS and 1% antibiotic-antimycotic cocktail (STR/Pen; Life Technologies Corporation, Carlsbad, CA), as described previously ( Cromeans et al, 2014 ; Esseili et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fecal filtrates from GII.4 Sydney[P16] and GII.4 Sydney[P4 New Orleans] human norovirus-positive fecal samples were prepared by passing clarified stool extracts through four serial filters (5, 1, 0.45, and 0.22 μm) as described previously ( Costantini et al, 2018 ) and stored at −70°C until the time of testing. Tulane virus was grown in LLC-MK2 cell line (ATCC CCL-7) cultured in Opti-MEM (Gibco Life Technologies, Grand Island, NY) supplemented with 2% FBS and 1% antibiotic-antimycotic cocktail (STR/Pen; Life Technologies Corporation, Carlsbad, CA), as described previously ( Cromeans et al, 2014 ; Esseili et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The TV stock was generated in the LLC-MK2 cell line (ATCC CCL-7, Gaithersburg, MD, USA) as described in our previous publications [8,9]. The stock virus was ultrafiltered using Amicon 100 KDa Ultra-15 centrifugal devices (Millipore, MA, USA) to semi-purify the virus from cell culture lysate and further concentrate the virus.…”
Section: Tulane Virus Stock Preparation and The Tcid50 Infectivity Assaymentioning
confidence: 99%
“…The stock virus was ultrafiltered using Amicon 100 KDa Ultra-15 centrifugal devices (Millipore, MA, USA) to semi-purify the virus from cell culture lysate and further concentrate the virus. The TCID 50 assay was performed as described in our previous publications [8,9]. The stock TV titer was ~6.5 log TCID 50 /mL.…”
Section: Tulane Virus Stock Preparation and The Tcid50 Infectivity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has shown that many factors enhance HuNoV persistence on the surface of lettuce leaves, including the presence of phytopathogens and physical damage [14,15,16]. The virus was also shown to internalize through the roots of lettuce seedlings and was detected by confocal microscopy inside the leaf mesophyll [17]. In addition, our group has shown that HuNoV GII.4 virus-like particles (VLPs) can bind specifically to lettuce cell wall carbohydrates extracted from leaves [16].…”
Section: Introductionmentioning
confidence: 99%